The Influence of Family Psycoeducation on the Ability of Families in Careing for Schizophrenia Patients in Sumberpucung Village Community Health Center, Sambigede Village Kecamatan Sumberpucung, District. Poor - Lingga Kusuma Wardani; Priyanto (Journal of Global Research in Public Health, 2022)
Schizophrenia sufferers usually tend to be unable to connect thoughts within themselves which results in the loss of ability and willingness to carry out activities, especially in aspects of fulfilling basic needs such as eating, sleeping and personal hygiene (Yosep, 2016). The inability of families and clients to carry out self-care can result in clients experiencing self-care deficits. The purpose of this study was to determine the effect of family psychoeducation on the ability of families to care for schizophrenics at the Sumberpucung Community Health Center, Sambigede Village, Sumberpucung District, Malang Regency. This study used a pre-experimental research design with a pretest posttest design approach. The population in this study was 100 families who cared for schizophrenia patients at Sumberpucung Health Center, Sambigede Village, Sumberpucung District, Malang Regency. A sample of 50 respondents was taken using the Simple Random Sampling technique. That is taking a simple random sample. The results of the research were that most (68%) of the respondents before being given psychoeducation were unable to care for schizophrenia patients, namely 34 people. Based on the Wilcoxon test, a p-value of 0.000 <alpha (0.05) was obtained. This indicated that H0 was rejected and H1 was accepted, meaning that there is an influence of family psychoeducation on the ability of families to care for schizophrenics at the Sumberpucung Health Center, Sambigede Village, Sumberpucung District, Malang Regency. In this study there is a Negative Rank, namely 28 respondents. Psychoeducation is very important to improve the ability of families to care for people with mental disorders, so that the quality of life for people with mental disorders is getting better.